La competitividad a nivel microeconómico de las PyMES manufactureras exportadoras de Michoacán, México y Jaén, España entre el 2008 y 2010 - Tafolla Manzo, Andrea Celeste (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The objective of the investigation is to know and to measure the variables that have been correlated with the competitiveness at micro-economic level of PYMES manufacturers michoacán exporters, Mexico; and compared with PYMES of the same rubri of Jaén, Spain in the period of 2008 -2010. Under the focus of the Systemic competitiveness, you seleccionarón two representative samples of PYMES in Michpacán (40) and in Jaén (33). To gather the information it was elaborated of a questionnaire with questions dicotónicas and ordinal scale of data. This way the method to examine the results was the coefficient of correlation of Spearman starting from which the first hypothesis test was elaborated to measure the association between the independent variables and the competitiveness

El objetivo de la investigación es conocer y medir las variables que se han correlacionado con la competitividad a nivel microeconómico de las PYMES manufactureras exportadoras de Michoacán, México; y comparadas con las PYMES del mismo rubro de Jaén, España en el periodo de 2008-2010. Bajo el enfoque de la competitividad Sistémica, se seleccionaron dos muestras representativas de PYMES en Michoacán (40) y en Jaén (33). Para recolectar la información se elaboró de un cuestionario con preguntas dicotónicas y escala de datos ordinal. Así el método para examinar los resultados fue el coeficiente de correlación de Spearman a partir del cual se elaboró la primera prueba de hipótesis para medir la asociación entre las variables independientes y la competitividad.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2012-0005; Competitividad empresarial; Sector manufacturero; Mejora; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/960